REPRESENTASI DALAM HIKAYAT SITI MARIAH VERSI SURAT KABAR BINTANG TIMUR - Susanto, Dwi (Balai Bahasa Jawa Timur, 2007)
The HSM BT indicated of the Self and the Other relation that was complex. The complexity could be seen at the character of representation. The phenomenon of representation was showed within ambivalence, hybrid, floating of identity, and hazy. The play and strategy were done in orde to get space and free from shackling and shadows of colonial power and bias. Strategy and representation of story telling, narrator position, identity political, and gender relation was to the be way to reach and change colonial bias. This paper aims to expose the power and domination of colonial space and time. This paper also shows colonial zone. This paper used postcolonial paradigm in particular representation the Self and the Other. This paper had concluded that the power and shadows of colonial always get space and time at relation and aspect human relation, gender, images, identity, etc. Each of way to avoid colonial shadows and bias always followed by another colonial of ways. The tone heterogeneity and plurality were taken as tolls to repress and lie of freedom way the Other